Cisplatin induces TRPA1-mediated mechanical allodynia in the oral mucosa. (January 2022) - Nakatomi, Chihiro; Hitomi, Suzuro; Yamaguchi, Kiichiro; Hsu, Chia-Chien; Seta, Yuji; Harano, Nozomu; Iwata, Koichi; Ono, Kentaro
Abstract: Objective: Cisplatin, a platinum-based anticancer drug, produces reactive oxygen species (ROS) in many cell types and induces mechanical allodynia in the hands and/or feet (chemotherapy-induced painful neuropathy: CIPN). In this study, we examined the possibility of inducing neuropathy in the oral region using oral keratinocytes and rats. Methods: Human oral keratinocytes (HOKs) were used to evaluate ROS generation after cisplatin application by a ROS-reactive fluorescent assay. In rats, after cisplatin administrations (two times), the trigeminal ganglion (TG) was investigated by electron microscopy and quantitative RT-PCR. Using our proprietary assay system, oral pain-related behaviors were observed in cisplatin-treated rats. Results: In rats, cisplatin administration reduced food intake and body weight. In electron microscopic analysis, glycogen granules in the TG were depleted following administration, although organelles were intact. In HOK cells, cisplatin significantly increased ROS generation with cell death, similar to glycolysis inhibitors. Cisplatin administration did not show any effects on Trpa1 mRNA levels in the TG. However, the same procedure induced hypersensitivity to mechanical stimulation and the TRPA1 agonist allyl isothiocyanate in the oral mucosa. Mechanical hypersensitivity was inhibited by the antioxidative drug α-lipoic acid and the TRPA1 antagonist HC-030031, similar to that of the hind paw. Conclusion: The present findings suggest that cisplatin induces TRPA1-mediated CIPN due to ROS generation in the oral region. This study will provide a better understanding of persistent oral pain in cancer patients. Highlights: Cisplatin induces mechanical allodynia in the oral region of rats. TRPA1 and ROS are involved in cisplatin-induced oral mechanical allodynia. Cisplatin increases ROS generation with cell death in human oral keratinocytes. Cisplatin decreases glycogen granules in the trigeminal ganglion neurons.